2021
DOI: 10.3889/oamjms.2021.5926
|View full text |Cite
|
Sign up to set email alerts
|

Food Consumption Patterns of Male and Female Undergraduate Students in Indonesia During New Normal Implementation of Pandemic Covid-19 Era

Abstract: AIM: This study aimed to analyze the description of Indonesian undergraduate students’ food consumption patterns during the COVID-19 period. METHODS: The design used was cross-sectional with random sampling technique. The correlation test was Chi-Square and analyzed using univariate. The respondents involved were 17–24 years old with 5924 persons; active undergraduate students. Questionnaires were distributed using Google form. RESULTS: The results indicated a relationship between gender and major, education l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
6
1
2
Order By: Relevance
“…The result of this study demonstrated that during the pandemic, West Java society consumes fruits and vegetables more often than before the pandemic. This result was under accordance with the previous research that showed good changes in the behavior of a society that is to eat vegetables more often [8], [30], [31]. Vegetables are an ingredient of food sources of antioxidants that can improve health [32].…”
Section: Discussionsupporting
confidence: 92%
“…The result of this study demonstrated that during the pandemic, West Java society consumes fruits and vegetables more often than before the pandemic. This result was under accordance with the previous research that showed good changes in the behavior of a society that is to eat vegetables more often [8], [30], [31]. Vegetables are an ingredient of food sources of antioxidants that can improve health [32].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it can be seen that most of the respondents have paid attention to the nutrition of the food consumed. This figure is higher when compared to research conducted in Surabaya, namely in adolescents at the State University of Surabaya, only 52% of the respondents had implemented a balanced nutrition pattern during this pandemic (Amaliyah et al, 2021;Kristiandi et al, 2021).…”
Section: Discussioncontrasting
confidence: 58%
“…Among the population-based survey studies, thirty-one were conducted through online surveys only ( 17 , 18 , 20 , 22 , 23 , 25 , 26 , 28 31 , 35 , 42 , 43 , 45 , 48 54 , 57 62 , 66 , 68 , 74 ), one was an in-person interview ( 56 ), three were telephone interviews ( 10 , 21 , 38 ), and two were both in-person and online surveys ( 19 , 36 ). Among the included studies, usage status of the interventions, including TCM ( n = 22) ( 27 , 32 34 , 37 , 39 , 40 , 44 , 47 , 55 , 63 65 , 67 , 69 73 , 75 77 ), functional food (supplements) or herbs ( n = 20) ( 17 24 , 29 , 36 , 38 , 43 , 49 52 , 57 59 ), mind-body practice or spiritual practice ( n = 9) ( 28 , 35 , 42 , 45 , 48 , 54 , 60 , 61 , 74 ), Ayurveda ( n = 2) ( 10 , 41 ), homeopathy ( n = 1) ( ...…”
Section: Resultsmentioning
confidence: 99%